Comparison of acute and prolonged effects of short-term foam rolling and vibration foam rolling on the properties of knee extensors - Kasahara, Kazuki; Konrad, Andreas; Yoshida, Riku; Murakami, Yuta; Sato, Shigeru; Koizumi, Ryoma; Thomas, Ewan; G Behm, David; Nakamura, Masatoshi (Biology of Sport, 2024)
Recently, Foam Rolling (FR) and Vibration Foam Rolling (VFR) have attracted attention in sports and rehabilitation fields. Previous studies have shown that FR and VFR acute interventions effectively increase the range of movement (ROM) and decrease tissue hardness. For application to sports and rehabilitation, it is necessary to compare the acute and prolonged effects of short duration FR and VFR. Therefore, this study aimed to compare and investigate the acute and prolonged (15 minutes) effects of short duration (30-s) FR and VFR interventions on knee extensors. The subjects were 14 male university students (22.4±1.0 years old), in which the knee extensors of the dominant leg were tested. In a cross over trial, 30-s of FR or VFR were performed with 2-s rolling of the anterior thigh (15 rolls). The frequency of VFR was 35 Hz. Measurements included knee flexion ROM, pain pressure threshold (PPT), tissue hardness, and countermovement jump height. The results of this study showed no interaction effects for all variables, but main time effects were observed for knee flexion ROM, PPT, and tissue hardness. Post-hoc tests showed that knee flexion ROM increased up to 10 minutes after the intervention. PPT significantly increased, and tissue hardness significantly decreased up to 15 minutes after intervention. This study showed that 30-s FR and VFR interventions effectively increased ROM, PPT, and decreased tissue hardness. The effects were prolonged up to 10–15 minutes after the intervention. The results of this study show no advantage of VFR over FR with acute short-term interventions.